2021
DOI: 10.3390/ijms22158195
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Impact of Creatine Supplementation on Depressive Symptoms, Brain Serotonin and SSRI Efficacy in an Animal Model of Treatment-Resistant Depression

Abstract: Background: Rates of major depressive disorder (MDD) increase with living at altitude. In our model, rats housed at moderate altitude (in hypobaric hypoxia) exhibit increased depression-like behavior, altered brain serotonin and a lack of antidepressant response to most selective serotonin reuptake inhibitors (SSRIs). A forebrain deficit in the bioenergetic marker creatine is noted in people living at altitude or with MDD. Methods: Rats housed at 4500 ft were given dietary creatine monohydrate (CRMH, 4% w/w, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Animal research suggests there may be a sex-dependent relationship regarding creatine and depression [ 110 , 112 , 113 , 114 ]. Dietary creatine appears to be more efficacious in female rats compared to male rats [ 110 , 112 ]; however, creatine in combination with other antidepressant drugs does appear to have some benefit in male rodents [ 114 ].…”
Section: Creatine and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal research suggests there may be a sex-dependent relationship regarding creatine and depression [ 110 , 112 , 113 , 114 ]. Dietary creatine appears to be more efficacious in female rats compared to male rats [ 110 , 112 ]; however, creatine in combination with other antidepressant drugs does appear to have some benefit in male rodents [ 114 ].…”
Section: Creatine and Mental Healthmentioning
confidence: 99%
“…Animal research suggests there may be a sex-dependent relationship regarding creatine and depression [ 110 , 112 , 113 , 114 ]. Dietary creatine appears to be more efficacious in female rats compared to male rats [ 110 , 112 ]; however, creatine in combination with other antidepressant drugs does appear to have some benefit in male rodents [ 114 ]. The use of creatine has also been investigated in other clinical models where depression is often observed as a secondary consequence of disease, or it results from the treatment.…”
Section: Creatine and Mental Healthmentioning
confidence: 99%
“…They showed that creatine treatment improved serotonin deficits in female rats at altitude and has antidepressant efficacy. In male rats at altitude, creatine alone is not antidepressant, while creatine combined with the selective serotonin reuptake inhibitors enhances brain serotonin levels and is an antidepressant (36).…”
Section: Discussionmentioning
confidence: 93%
“…The antidepressant effect of creatine on the tail suspension test is suppressed by compounds that inhibit serotonin synthesis and increased by co-administration with selective serotonin reuptake inhibitors, like fluoxetine (35). Another study by Kanekar, Ettaro (36) showed that dietary oral creatine monohydrate supplementation can improve brain bioenergetic damage at altitude in rats of both genders and has gender-based effects on regional brain serotonin levels as well as antidepressant effects. They showed that creatine treatment improved serotonin deficits in female rats at altitude and has antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical studies have reported sexual dimorphisms in the severity and evolution of perinatal encephalopathy and responses to treatment [ 67 , 68 , 69 , 70 ]. There are limited data indicating sex-specific differences in creatine uptake in the adult brain [ 71 ]. However, whether these differences exist in the perinatal brain and are physiologically significant enough to impact on HIE should be considered.…”
Section: Discussionmentioning
confidence: 99%